Prognostic analysis of elderly patients with pathogenic microorganisms positive for sepsis-associated encephalopathy - Shi, Xiaopeng; Xu, Lijun; Jing, Lijuan; Wang, Zehua; Zhao, Lina; Zhao, Xiangmei (Frontiers in Microbiology, 2024)
ObjectivesSepsis-associated encephalopathy (SAE) has a high incidence and mortality, especially for elderly patients and patients who are positive for pathogenic microbial infection, this study explored the prognostic factors influencing the prognosis of elderly patients with pathogenic microorganisms positive of sepsis-associated encephalopathy.MethodsPatients with SAE and pathogenic microbiology positive were included in this study from Medical Information Mart for Intensive Care IV (MIMIC IV) database. The main results of this study was analyzed the 28-day mortality rate of patients with pathogenic microorganism positive and SAE by Wilcoxon, Kaplan–Meier curve and other methods.ResultsThis study found that older patients with SAE had higher mortality at 28 and 90 days compared with non-older patients with SAE. Klebsiella pneumoniae and Pseudomonas aeruginosa infection, the level of APTT and lactate and SAPS III score were independent risk factors for 28-day mortality in elderly patients with SAE, among them, Klebsiella pneumoniae and Pseudomonas aeruginosa infection had the best sensitivity (0.893; 0.931) in assessing elderly patients with pathogenic microorganisms positive and SAE; the SAPS III score had the highest AUC (0.681) value and specificity (0.761) in assessing elderly patients with pathogenic microorganisms positive and SAE.ConclusionThe older patients with SAE had a poor prognosis, the elder patients with pathogenic microorganisms positive and SAE with high levels of APTT and lactate and SAPS III score and Klebsiella pneumoniae and Pseudomonas aeruginosa infection should be closely monitored and treated aggressively.